2003
DOI: 10.1590/s1413-86702003000100009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological analysis of children and adolescents with tuberculosis in Bahia, Brazil

Abstract: We reviewed the clinical and radiological characteristics of tuberculosis (TB) in children and adolescents at the Hospital Especializado Octávio Mangabeira, (HEOM) in Salvador, Bahia. This study included 275 TB patients aged 1 to 15 years seen between January 1990 and November 2001. Standardized forms were filled out on the basis of a review of patient records and x-rays. Through a retrospective and descriptive analysis, it was found that 51.6% were male, 35.3% were aged 1 to 5 years, 28% were aged 6 to 10 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
16
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 5 publications
(7 reference statements)
8
16
3
Order By: Relevance
“…Our results are consistent with the various studies described in literature [8,9,11,13,15] In our study CNS tuberculosis accounted for 11.8% cases, this was comparable with study of Pontual et al [16] where 16.67% cases were had isolated CNS tuberculosis. Lymphadenopathy was seen in 23.5% and isolated lymphadenopathy was seen in 1.96% cases.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our results are consistent with the various studies described in literature [8,9,11,13,15] In our study CNS tuberculosis accounted for 11.8% cases, this was comparable with study of Pontual et al [16] where 16.67% cases were had isolated CNS tuberculosis. Lymphadenopathy was seen in 23.5% and isolated lymphadenopathy was seen in 1.96% cases.…”
Section: Discussionsupporting
confidence: 94%
“…Primary complex was most common finding on X ray accounting for 36(50.7%) cases and 15(21.1%) cases showed pleural effusion. Similar to study by Franco et al [8 ] observed primary complex in 44.3% cases. History of BCG vaccination was positive in 87.42% cases and 13.72% of those vaccinated did not have a BCG mark on examination.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations